Making the case : how to be your own best advocate - Guilfoyle, Kimberly (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2015)
When Kimberly Guilfoyle was just ten years old she lost her mother to a battle with leukemia. Her father knew that he couldn't possibly anticipate all the needs of his children alone so he set out to teach Kimberly how to advocate for herself and for her younger brother. He instructed her on how to ask for what she needed and how to build a strong case to get it. Those valuable childhood lessons helped Kimberly become the quick-thinking spitfire she is today. In Making the Case she weaves stories and anecdotes from her life and career with specific strategies that can help anyone set clear goals, communicate more effectively, and come out on top in any situation.
Introduction -- Part I: Advocating At Work -- Chapter 1 How to Land the Best Job in the World (for You) -- Chapter 2 Dressing for the Part -- Chapter 3 Asking for a Promotion -- Chapter 4 Standing Up for Your Ideas -- Chapter 5 Working as a Team -- Chapter 6 Changing Careers -- Chapter 7 Playing by the Rules -- Part II: Advocating At Home -- Chapter 8 The Power of Friendships -- Chapter 9 Dating and Marriage -- Chapter 10 Money and Relationships -- Chapter 11 Supporting Your Spouse -- Chapter 12 Teaching Kids to Advocate for Themselves -- Chapter 13 Making Divorce Work for Everyone Involved -- Chapter 14 Avoiding Family Drama -- Chapter 15 Caring for Aging Parents -- Chapter 16 Help! How to Ask for It, Receive It, and Give It -- Acknowledgments -- Index.
Includes index.
Keywords: Guilfoyle, Kimberly; Success; Conduct of life